Thermal and Nonthermal Effects in Plasmon‐Mediated Electrochemistry at Nanostructured Ag Electrodes. Issue 17 (3rd March 2020) - Ou, Weihui; Zhou, Binbin; Shen, Junda; Lo, Tsz Wing; Lei, Dangyuan; Li, Shengliang; Zhong, Jing; Li, Yang Yang; Lu, Jian
Abstract: Hot carriers (HCs) and thermal effects, stemming from plasmon decays, are crucial for most plasmonic applications. However, quantifying these two effects remains extremely challenging due to the experimental difficulty in accurately measuring the temperature at reaction sites. Herein, we provide a novel strategy to disentangle HCs from photothermal effects based on the different traits of heat dissipation (long range) and HCs transport (short range), and quantitatively uncover the dominant and potential‐dependent role of photothermal effect by investigating the rapid‐ and slow‐response currents in plasmon‐mediated electrochemistry at nanostructured Ag electrode. Furthermore, the plasmoelectric surface potential is found to contribute to the rapid‐response currents, which is absent in the previous studies. Abstract : A strategy bypassing inaccuracies in local temperature measurement was invented for quantitatively disentangling hot electron effect and thermal effect in plasmon‐mediated electrochemical reactions, unveiling the dominant and potential‐dependent role of thermal effect at nanostructured Ag electrodes.